Seismic upgrading of exterior reinforced concrete frame with small column and joint area using externally attached steel column - Anawat Thipprasert (2019)
© 2019, Brazilian Association of Computational Mechanics. All rights reserved. This paper presents cyclic load test of five exterior reinforced concrete frames. All the specimens represent a substandard single-span, low-rise reinforced concrete frame building which behaves a weak column-strong beam mechanism under a strong seismic loading. The first three exterior frames M1, M2 and M3 were designed for the joint shear critical to investigate the effect of joint reinforcement. They are similar except the joint reinforcement detailing. The fourth specimen M4 was an exterior frame with a very small column member. The fifth specimen U5 was the seismic upgrade of M4 specimen using externally attached steel column. From the first three tests, the increase in shear capacity due to the reinforcement provided in the beam-column joint was negligible when the column size was small leading to high joint shear stress. The shear capacity of the specimens was agreed well with the calculation formula provided by ACI318 (ACI, 2008) ignoring the contribution from the reinforcement. The upgraded frame markedly indicated the increased capacity of 2.02 times of the strength of M4 specimen. However, the ductility of the upgraded frame was decreased. It was the result from that the failure mode of the specimen was shifted from the joint failure to the column damage at the section next to the end of the attached steel column.